Experimental Tests of the Moms Economicus: Implications of Research on Islamic Economics (American Journal of Islam and Society, 1999)
This article has multiple objectives. It seeks to identify those assumptionsof neoclassical economics which are vindicated by experimentaltests and those which fail such tests. The author tries to simultaneouslyexpose the limitations of neoclassical economics and Islamic economicsby pointing out that some assumptions of the rational choice modelfail while others, often ignored by Islamic economists, are proven valid.The article also seeks to summarize the results of experimental testingabout agent behavior under a controlled environment. The author hopesthat this initiative will encourage Islamic economists to use experimentalmethods as a means for testing their theoretical assumptions. Theauthor concludes that human agents are neither as self-regarding as thehomo economicus model predicts nor are they as other-regarding as themodel homo Islamicus predicts.